Quorn and district centenary, 1878-1978 - Quorn Centenary Book Committee (Blackwood, S.A. : Lynton, 1978)
Includes map of tribes in area; Aboriginal place names list and photographs of artifacts collected in region.
Index.
Bibliography: p.234.
Keywords: South Australia. Quorn region, 1878-1978.; Language - Vocabulary - Place names; Technology; Quorn Region (S.A.) -- History; Quorn (SE SA SI54-01)